Respon Pertumbuhan dan Produksi Senyawa Antioksidan pada Kalus Hibiscus sabdariffa L. dari Eksplan yang Berbeda secara in vitro - Noviati, Agustin; Nurchayati, Yulita; Setiari, Nintya (JURNAL SAINS DAN MATEMATIKA, 2014)
Ascorbic acid and carotenoid are secondary metabolites found in roselle, which show antioxidant activity. These compounds can be obtained from callus induced by several kinds of explants. The aims of this experiment is to study callus growth from explants which can encourage high level of antioxidant compounds. The callus was obtained from difference organ, i.e. section of leaf, petiole and flower sepal. Sterilized explants were planted in MS (Murashige&Skoog) combined with 2 mg/L Naphtalene Acetic Acid (NAA) dan 5 mg/L Benzyl Adenin (BA). This experiment has been conducted by completly randomized design with 5 replicates. Besides fresh weight callus, callus respons from each explants were analyzed descrptively. Ascorbic acid and carotenoid content were analyzed qualitatively and quantitatively by titration and spectrophotometric respectively. The results showed that all kinds of explant dedifferentiated into callus which antioxidant content. Callus from leaf section had the higgest fresh weight with high level ascorbic acid. Whereas the higgest carotenoid level was obtained from callus-derived flower sepals. It conclused that in vitro callus was useful for producing plant biochemical compounds. Keywords : Callus induction, antioxidant agents, explants, ascorbic acid, cartenoid